The dimensional structure of the functional abilities in cases of long-term sickness absence - Mulders Henny PG; Broersen Jake PJ; Schellart Antonius JM; van der Beek Allard J (BMC, 2011)
Abstract Background The health problems that working people suffer can affect their functional abilities and, consequently, can cause a mismatch between those abilities and the demands of the work, leading to sickness absence. A lasting decrease in functional abilities can lead to long-term sickness absence and work disability, with negative consequences for both the worker and the larger society. The objective of this study was to identify common disability characteristics among large groups of long-term sick-listed and disabled employees. Methods As part of the disability benefit entitlement procedure in the Netherlands, an insurance physician assesses the functional abilities of the claimant in a standardised form, known as the List of Functional Abilities (LFA), which consists of six sections containing a total of 106 items. For the purposes of this study, we compiled data from 50,931 assessments. These data were used in an exploratory factor analyses, and the results were then used to construct scales. The stability of dimensional structure of the LFA and of the internal consistency of the scales was studied using data from 80,968 assessments carried out earlier, under a slightly different legislation. Results Three separate factor analyses carried out on the functional abilities of five sections of the LFA resulted in 14 scale variables, and one extra scale variable was based on the items from the sixth section. The resulting scale variables showed Cronbach's Alphas ranging from 0.59 to 0.97, with the exception of one of 0.54. The dimensional structure of the LFA in the verification population differed in some aspects. The Cronbach's Alphas of the verification population ranged from 0.58 to 0.97, again with the exception of the same scale: Alpha = 0.49. Conclusion The differences between the dimensional structures of the primary data and the earlier data we found in this study restrict the possibilities to generalise the results. The scales we constructed can be utilised to produce a compact description of the functional abilities of groups of claimants in the Netherlands. Moreover, the matching work demands can be used to identify jobs low on those demands as being the most accessible for the specific type of disabled employees, particularly severely disabled individuals.